Pengembangan Kemampuan Pemecahan Masalah Matematis melalui Habit of Thinking Interdependently - Rahmadeni, Fevi; Tomi Ariyanto; Patri Ayu; Aulia Uswatun Hasanah (Institut Agama Islam Negeri Curup, 2020)
Like the human body, problem solving is the heart of mathematics. Problem solving ability is a capital for students to develop and explore themselves further in mathematics learning. This article aim to explain the development of students' mathematical problem solving abilities through Habit of Thinking Interdependently (HTI). This type of research is literature review where the authors analyze and draw conclusions from several relevant references related to HTI. HTI the attitude of students towards learning mathematics in the form of the habit of thinking together in groups. The conclusions obtained indicate that students' mathematical problem solving abilities can be developed through HTI.